Le Français Sur Objectif Universitairedans Le Contexte Algérien: Réalité, Enjeux ET Perspectives - Belkacem, Mohammed Amine (جامعة مولود معمري تيزي وزو - مخبر الممارسات اللغوية, 2021)
This paper deals with the problem of the availability of specialized trainers at the Algerian university. By referring to the different profiles of teachers of French specialty, we note the existence of a single profile in this case a FLE teacher providing a terminology course. In order to meet the new needs of the students, the university must call on other profiles through a massive didactization of the different courses requiring a specific French. The objective being the urgent training of teachers mastering the practical and vehicular aspect of French as well as the way to deliver it (methodology) in other words, French on Academic Objective (FOU).
Keywords: المنهج التربوي -- اللغة الفرنسية -- المعلمين الفرنسيين